Assessment of Planar Transmission Line with Stub for Measuring Water Content in Power Transformer Oil - Daniel A. B. Fonseca; Luís G. da S. Costa; Wesley M. Cantarino; Ulysses R. C. Vitor (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract This study investigates the effectiveness of employing Planar Transmission Lines (PTL) with stubs to determine the water content in transformer oils. The research aims to elucidate how transmission responses along the line can provide valuable patterns for oil characterization. Notable results were achieved, particularly in identifying representative frequencies for each range of S21 scattering parameters, enabling the derivation of well-fitted linear expressions for the data. These findings suggest promising potential for the practical application of this approach. This study contributes not only to the understanding of the proposed technique but also to the stimulation of subsequent research aiming to enhance and consolidate this analytical methodology.